Survival Outcomes Following Discontinuation of Ipilimumab and Nivolumab for Advanced Melanoma in a Population-based Cohort. Issue 12 (December 2021) - Ksienski, D.; Truong, P.T.; Wai, E.S.; Croteau, N.S.; Chan, A.; Patterson, T.; Clarkson, M.; Hackett, S.; Irons, S.; Lesperance, M.
Abstract: Aims: Induction ipilimumab and nivolumab followed by maintenance nivolumab improve overall survival compared with ipilimumab alone in patients with advanced melanoma, but immune-related adverse events (irAE) occur commonly. The need for induction discontinuation because of irAE and the relationship between irAE and survival in non-trials patients are unclear. Materials and methods: Patients with unresectable stage III–IV melanoma receiving first-line combination immunotherapy at one of six centres between December 2017 and February 2020 outside of trials were identified retrospectively. Landmark 12-week Kaplan–Meier analyses and log-rank tests were used to evaluate associations between discontinuation of induction therapy on overall survival and time to treatment failure (TTF). Multivariable analysis of factors influencing overall survival and TTF was undertaken. Results: Among 95 patients, the median age was 62 years, 38.9% had Eastern Cooperative Oncology Group performance status ≥1 and 22.1% had brain metastases. The median follow-up for the whole cohort was 19.8 months by the reverse Kaplan–Meier method. Any grade and grade 3–4 irAE were noted in 78.9% and 44.2% of the cohort, respectively. 44.2% of patients completed induction immunotherapy, whereas 41.1% did not due to irAE. Twelve-week landmark overall survival and TTF were similar in patients who completed induction versus those who did not due to irAE. On multivariable analysis, any grade irAE (versus none) was associated with longer overall survival (hazard ratio = 0.35, 95% confidence interval 0.15–0.82, P = 0.02) and TTF (hazard ratio = 0.38, 95% confidence interval = 0.17–0.81, P = 0.01). Grade 3–4 irAE correlated with longer TTF (hazard ratio = 0.45, 95% confidence interval = 0.20–1.01, P = 0.05). Conclusion: In this population-based cohort, discontinuation of induction immunotherapy as a result of irAE did not adversely affect overall survival or TTF. irAE observed during ipilimumab and nivolumab induction were associated with improved survival outcomes. Highlights: In this population-based study, incidence of immune-related adverse events (irAE) was similar to trials. 41.1% of patients discontinued induction immunotherapy for advanced melanoma due to irAE. Survival outcomes were similar for patients who did and did not complete induction due to irAE. Early onset irAE were associated with improved overall survival and time to treatment failure.